Phylogenomic species delimitation in microendemic frogs of the Brazilian Atlantic Forest - Pie, Marcio R.; Bornschein, Marcos R. [UNESP]; Ribeiro, Luiz F.; Faircloth, Brant C.; McCormack, John E. (Elsevier B.V., 2019)
The advent of next-generation sequencing allows researchers to use large-scale datasets for species delimitation analyses, yet one can envision an inflection point where the added accuracy of including more loci does not offset the increased computational burden. One alternative to including all loci could be to prioritize the analysis of loci for which there is an expectation of high informativeness. Here, we explore the issue of species delimitation and locus selection with montane species from two anuran genera that have been isolated in sky islands across the southern Brazilian Atlantic Forest: Melanophryniscus (Bufonidae) and Brachycephalus (Brachycephalidae). To delimit species, we obtained genetic data using target enrichment of ultraconserved elements from 32 populations (13 for Melanophryniscus and 19 for Brachycephalus), and we were able to create datasets that included over 800 loci with no missing data. We ranked loci according to their number of parsimony-informative sites, and we performed species delimitation analyses using BPP with the most informative 10, 20, 40, 80, 160, 320, and 640 loci. We identified three types of phylogenetic node: nodes with either consistently high or low support regardless of the number of loci or their informativeness and nodes that were initially poorly supported where support became stronger as we included more data. When viewed across all sensitivity analyses, our results suggest that the current species richness in both genera is likely underestimated. In addition, our results show the effects of different sampling strategies on species delimitation using phylogenomic datasets.
Keywords: Anura; Terraranae; Brachycephalus; Melanophryniscus; Ultraconserved elements; UCEs